Hubungan Tingkat Pengetahuan Dengan Minat Pasien Melakukan Perawatan Saluran Akar Di RSUD Kab. Banggai - Aulyah, Dwi Rezky (Jurnal Ilmiah Amanah Akademika, 2023)
Root canal treatment is a type of treatment that cannot be completed in one visit. Therefore, it really requires patient compliance to be able to complete root canal treatment. This type of research is analytical survey research. The research design used was quantitative with a cross sectional approach. The sampling technique in this research was non-probability sampling using accidental sampling of 80 people. Respondents had a high level of knowledge with high interest, namely 52 people (65%). Data analysis was carried out using the Kendall's tau formula and obtained a significance value of 0.002 < 0.05. There is a relationship between the patient's level of knowledge and the patient's interest in carrying out root canal treatment at the Banggi District Hospital, with a sufficient correlation value of 0.264. There is a sufficient relationship between the patient's level of knowledge about root canal treatment and the patient's interest in having root canal treatment at the District Hospital. Banggai.